Ensuring accountability in modern trade policy - Jürgen Matthes; Ilaria Maselli (Institut der deutschen Wirtschaft (IW), 2017)
Attempts to foster trade liberalisation with a new generation of trade agreements aimed at lowering non-tariff barriers face opposition among the general public. Many fear that trade liberalisation risks lowering the level of protection embedded in regulations that are aimed at safeguarding social rights, health and the environment. Such criticism cannot be ignored. As we argue in this paper, by clarifying its view on this issue, the EU can further strengthen the position in fora like the G7 and the G20 where the topic of trade is currently under discussion. But along which lines? Regulatory cooperation, in the context of the new generation of trade agreements, is promising, reasonable and controllable. If done correctly, regulatory cooperation will benefit consumers and not threaten consumer protection. However, a regulatory cooperation body needs transparency and a set of rules to be fully accountable to EU citizens. Looking at the way the same issue was dealt with in the context of monetary policy and independent central banks, we propose a mix of provisions that aim at defining a clear mandate, enforcing transparency of operations and establishing a reputation.
Keywords: F13; F6; E42; 330